A case study of the integration of ICT in teaching and learning in a smart school in Sabah - Goh, Lay Huah (2007)
This research investigates teachers’ views of their use of ICT in teaching and learning (T&LICT). The objective of this research was to study in depth the thoughts, beliefs and opinions of the teachers’ attempt towards pedagogical improvement as part of the Smart School Project. Specifically this research examines and describes the teachers’ implementation of T&LICT in the classroom in terms of the instructional practice, the instructional roles and the instructional environment. A case study research methodology is employed. The case is Sekolah Menengah Bestari (a psuedonym), which is a Smart School in Sabah. Analysis of data from 52 survey questionnaires complemented the qualitative data from the 13 interviews and 3 observations, as well as document analysis. Findings indicated that hardware and software technology infrastructure were available to support the T&LICT implementation. Nevertheless, the teachers felt it was not enough to implement T&LICT effectively. It was estimated that about half of Sekolah Menengah Bestari staff, mainly Bestari and ETeMS teachers, implemented T&LICT. Findings indicated that teacher practices were little changed. IT was used mainly to support the existing teacher-directed and teacher-centered approach. The role of the teacher extended to that of facilitating without releasing control of lesson to the students.